Pengaruh Perkembangan Sistem Informasi Manajemen Pendidikan (SIMDIK) dalam Meningkatkan Kinerja Guru - Nuraini, Jihan; Hanifah, Yasmin Rizky (Innovative: Journal Of Social Science Research, 2024)
In this era of rapid technological development, the education sector is one of the fields that utilize this opportunity to develop Management Information Systems (MIS) to improve education services. The use of Education Management Information System (SIMDIK) has been used to ensure that it can help teachers improve the quality of teaching, because teachers are an important component in the education process. This research uses the literature study method to obtain information and understanding related to the influence of SIMDIK in improving teacher performance. The results show that SIMDIK has an important role in improving teacher performance by providing better access to information, facilitating monitoring of student progress, managing administrative tasks more efficiently, and improving collaboration and communication. However, there are also challenges that still need to be addressed such as adequate infrastructure, the training needed for teachers to use the system effectively, and the need for good data security to keep student information protected.